Pengaruh Umur Panen terhadap Hasil dan Mutu Benih Kacang Panjang (Vignasinensis L.) - NI KADEK DWIK PRADNYAWATI; I GUSTI NGURAH RAKA; I KETUT SIADI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
The Effect of Harvesting Age on Seeds Production and Seeds Quality of Long Bean Seeds (Vigna sinensis L.) This research was conducted in January 2018 until May 2018 in Subak Sedang, Angantaka Village, Abiansemal District, Badung, Bali. This research aimedto determine the effects of time of harvesting after flowering on Long Bean seed physiological maturity and quality. This research in a one factor research with 3 differences of age of harvesting. The three age of harvesting : P1 (23 days after flowering), P2 (26 days after flowering), and P3 (29 days after flowering). Theresearch used a randomized block design (RBD) with 9 replications. Observations variables were made on number of pods, number of pithy seeds, weight of seeds per hectare, weight of 1000 seeds, viability and vigor. The results showed that the treatments of age of harvesting P2 (26 DAF) had an effect on the seed production and quality.